Implementation of the Cardiac Arrest Sonographic Assessment (CASA) protocol for patients with cardiac arrest is associated with shorter CPR pulse checks. (October 2018) - Clattenburg, Eben J.; Wroe, Peter C.; Gardner, Kevin; Schultz, Cody; Gelber, Jon; Singh, Amandeep; Nagdev, Arun
Abstract: Objective: We aim to evaluate whether implementation of the "Cardiac Arrest Sonographic Assessment" (CASA) protocol reduces the duration of interruptions in CPR during resuscitation of cardiac arrest (CA) compared to the pre-intervention period. Methods: This was a quasi-experimental pre and post intervention study completed over 19 months in an urban Emergency Department. CA resuscitations were filmed and analyzed with respect to pulse check duration and use of point-of-care ultrasound (POCUS). After one year, an intervention was implemented: ED residents and faculty were taught the CASA protocol and instructed on how to implement it within CA resuscitation. The primary outcome was the difference in CPR pulse check duration between the pre and post intervention period. Videos from pre and post intervention CA resuscitations were coded by two reviewers. Results: Data was collected prospectively for 267 sequential cardiac arrests. 38 pre-intervention and 45 post-intervention resuscitations were videoed and included in analysis. Both groups had a median of 3 pulse checks and 2 POCUS exams performed per code. CPR pulse checks involving POCUS exams were 4.0 s (95%CI 1.7–6.3) shorter in the post-intervention group than in the pre-intervention group. CPR pause durations were 3.1 s (95%CI 0.7–5.6) shorter when the ultrasound probe was placed on the chest before stopping CPR compared to placement after stopping CPR, and 3.1 s (95%CI 0.6–5.6) shorter when an ED ultrasound fellowship trained faculty was present compared to non-ultrasound fellowship faculty. The proportion of pulse checks with ultrasound use increased from 64% before the intervention to 80% after the intervention. Conclusion: In this pre and post-intervention study, the implementation of a structured algorithm for ultrasound use during cardiac arrest significantly reduced the duration of CPR interruptions when ultrasound was performed.